INDIGOFERA GLANDULOSA WENDLE (BARBADA) ANOVERLOOKEDNUTRITIONALPLANT:ACRITICALREVIEW (International Journal of Food and Nutritional Sciences, 2022)
In the present paper the research articles related to Indigoferaglandulosawendl. belonging tofamily Fabaceae were selected to critically review on various aspects, as per the articles accessed it can beconcluded that, IndigoferaglandulosaWendle. is small herb, familiar as a nutritional plant with a numberof vernacular names. It is widely distributed in India, Indonesia and North Australia. It produces seeds richinvaluablefoodingredientssuchascarbohydrates,protein,vitamin,andessentialaminoacids.Itdescribed as a nourishing food for humans and possess a qualities of a tonic in Indian medicine. The greenpart of plant can be used as a forage for domestic animals. In India, tribal collect the seeds from wildpopulationand use it as famine food.Theseed flour is use by locals and tribal for makingchapattis orbread roasted rotti. This literature survey indicated that, IndigoferaglandulosaWendl. is nutritionallybeneficialbutunfortunatelyitisneglectedunderutilizedplantspecies.Duetolackofattentionthepotentialvalue is underestimated and maynotproperlyexploited.